Modern practices in electrophoretic deposition to manufacture energy storage electrodes. (18th May 2022) - Chakrabarti, Barun Kumar; Gençten, Metin; Bree, Gerard; Dao, Anh Ha; Mandler, Daniel; Low, Chee Tong John
Summary: The applications of electrophoretic deposition (EPD) to the development of electrochemical energy storage (EES) devices such as batteries and supercapacitors are reviewed. A discussion on the selection of parameters for optimizing EPD electrode performance, such as light‐directed EPD, co‐deposition of active materials such as metal oxides and materials manufactured with high porosity and fibrous properties is highlighted. Additionally, means for overcoming obstacles in the improvement of the mechanical properties, conductivity and surface area of EES materials are discussed. The exceptional benefits of EPD such as low cost, small processing time, simple apparatus requirements, homogeneous coatings, binder‐free deposits and selective modification associated with thickness and mass loadings leading to effective EES electrode materials are highlighted. Finally, EPD processes have evolved as modern manufacturing tools to produce technologically improved solid electrolytes and separators for lithium‐ion and/or sodium‐ion batteries, and further research and development programmes are encouraged towards industrialisation. Abstract : Electrophoretic deposition can be effectively used to manufacture highly tailored and functional electrodes for a range of electrochemical energy storage applications.